Anti-diabetic Activity of Phloretin Against Maltase-glucoamylase Using Docking, Pharmacokinetics and Pharmacophore Studies - Miah Roney; Mohd Fadhlizil Fasihi Mohd Aluwi (Journal of Chemistry Letters)
A metabolic condition known as diabetes mellitus is characterized by hyperglycemia brought on by either inadequate insulin production, resistance to insulin action, or both. The anti-diabetic medications that are now on the market either impact how much glucose is absorbed and excreted or how much insulin is secreted without affecting insulin resistance. This study used in-silico methods to assess the efficacy of phloretin as anti-diabetic drug against maltase-glucoamylase. Phloretin displayed strong binding to the maltase-glucoamylase protein with good docking scores (-7.4 kcal/mol), as opposed to co-crystallized ligand (-6.2 kcal/mol). In terms of physicochemical qualities, drug-likeness, and medicinal chemistry properties, Phloretin also performed best. The results of molecular docking and data acquired from pharmacokinetic characteristics of phloretin may be used further for the creation of newer maltase-glucoamylases with potential anti-diabetic properties and improved pharmacokinetic profiles.